Current Topics in Malaria - Rodriguez-Morales, Alfonso J. (IntechOpen, 2016)
Malaria is still the main vector-borne parasitic disease in the world. Fortunately, elimination of this disease was achieved in multiple countries during the last decades. During the last decade, a significant reduction of malaria in the Americas was achieved. Nevertheless, many challenges still are ahead in order to reach a higher control and to continue in the elimination toward a world free of malaria in the next decades. This book tries to update the significant epidemiological and clinical research in many aspects with a multinational perspective. This book with 20 chapters is organized into 5 major sections: (I) Clinical and Epidemiological Aspects, (II) Basic Science, (III) Therapeutics and Antimalarials, (IV) Vaccines, and (V) Entomology and Vector Control.